The L-Total Graph of an L-Module. (17th October 2011) - Ebrahimi Atani, Reza
Abstract : LetL be a complete lattice. We introduce and investigate theL -total graph of anL -module over anL -commutative ring. The main purpose of this paper is to extend the definition and results given in (Anderson and Badawi, 2008) to more generalize theL -total graph of anL -module case.